Angiogenic Marker Prognostic Models in Pregnant Women With Hypertension. Issue 3 (March 2020) - Perry, Helen; Binder, Julia; Kalafat, Erkan; Jones, Stuart; Thilaganathan, Basky; Khalil, Asma
Abstract : Angiogenic markers such as PlGF (placental growth factor) and sFlt-1 (soluble Fms-like tyrosine kinase-1) have been shown to be useful for predicting adverse outcome in women suspected of having preeclampsia. The aim of the current study was to evaluate the prognostic value of angiogenic markers and maternal risk factors in pregnant women with hypertension. This was a prospective study of pregnancies complicated by preeclampsia, gestational hypertension, or chronic hypertension presenting to 1 of 2 tertiary referral hospitals between May 2013 and May 2018. Maternal characteristics along with blood samples for angiogenic marker analysis were obtained from participants. The primary outcome was delivery related to preeclampsia within 1 and 2 weeks. In total, 302 women with hypertension were included in the study cohort. The baseline model included maternal body mass index, mean arterial pressure, and clinical diagnosis at the time of assessment. The use of sFlt-1/PIGF ratio combined with the baseline model significantly improved the area under the curve values for predicting delivery within a week (0.83 versus 0.88; P =0.025) or in 2 weeks (0.86 versus 0.93; P =0.001) due to preeclampsia-related events in gestational ages <35 weeks. The magnitude of increase in accuracy was 7.9% (−0.5% to 16.4%, posterior probability of increase: 96.7%) for sFlt-1/PlGF ratio. Our results emphasize the additive value of angiogenic biomarkers and the superior performance of a continuous scale of sFlt-1/PlGF ratio in the model. The added utility of angiogenic markers diminishes after 35 weeks' gestation. Abstract : Supplemental Digital Content is available in the text.